Istiqra al-al-ma’nāwī; multicultural judicial reasoning - Isman Isman; Yahya Yahya (State Islamic University of Salatiga, 2022)
This article offers the istiqra’ al-ma’nāwī as multicultural-based judicial reasoning to answer the gap between the monocultural pattern of norms required by the codification of law and the multicultural based social-structure of Indonesian society. By using a legal philosophy approach, this study concludes that istiqra’ al-ma’nāwī is oriented to balance the interests (al-wasīlah) and the needs (al-ghāyah) as the basic framework for distinguishing relative and absolute values of law. The judicial reasoning style offered by istiqra’ al-ma’nāwī can be operationalized through moderating ethical contestation and formulating justice and legal certainty based on multiculturality. The operationalization is carried out through three stages: The first is konstatiring stage, where the judges use social reintegration as an optic to see if there is disrupted social risk, like identity superiority motives. The second is separating the original from the derivative goals. The original legal goal is to protect the rights of marginalized communities and equality, while the derivative legal goal is access to welfare and the rights of impunity. The third is konstituir stage, by considering the significance of social control outside the legal aspect.